2001
DOI: 10.1046/j.1365-2141.2001.02923.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tissue factor pathway inhibitor activity in patients with primary antiphospholipid syndrome

Abstract: Summary. The association between antiphospholipid antibodies and an increased risk of thrombosis in antiphospholipid syndrome (aPS) patients is probably caused by numerous mechanisms, including the effects of antibodies to phospholipid-binding proteins such as b 2 -glycoprotein I and prothrombin. In this study, we investigated the inhibition of tissue factor pathway inhibitor (TFPI) in 33 patients with primary antiphospholipid syndrome (PAPS). TFPI was measured in PAPS patients using an amidolytic assay, depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 16 publications
4
33
1
2
Order By: Relevance
“…Adams et al [124] have recently confirmed their previous data about the inhibitory effect of IgG fractions from APS against TFPI activity. The purified IgGs, however, demonstrated a variable ability to interfere with TF-induced in vitro thrombin generation.…”
Section: Annexin A5supporting
confidence: 57%
“…Adams et al [124] have recently confirmed their previous data about the inhibitory effect of IgG fractions from APS against TFPI activity. The purified IgGs, however, demonstrated a variable ability to interfere with TF-induced in vitro thrombin generation.…”
Section: Annexin A5supporting
confidence: 57%
“…This could be attributed to the LA influence on the lag time, as the majority of APS patients were LA positive [18], or could reflect the effect of other aPL [18,35], particularly as prolonged lag times in the PNP mixing studies were limited to the 12 triple aPL positive APS patients. The presence of other antibodies found in APS patients, such as those directed against protein C, FX, FVII, tissue factor pathway inhibitor, that mainly have an effect on the initiation phase of coagulation, may also influence TG [34,[38][39][40]. Notably, TG testing highlighted a small subgroup of four APS patients (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…APL antibodies have been demonstrated to induce a procoagulant state through endothelial cell, monocyte, and platelet activation, inhibition of antithrombotic proteins such as tissue factor pathway inhibitor and protein C, activation of complement, and inhibition of proteins of the fibrinolytic pathway, including plasminogen and tissue-type plasminogen activator (t-PA) [1,[10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%